Coherence in global economic policy-making : report (2011)- (WTO GenevaCH, 2011)
Reviews the mandates and activities of several international agencies and inter-governmental arrangements, determines that they do operate with overlapping and related mandates which adds to the imperative of securing adequate coordination and coherence among all the entities concerned.
Keywords: ECONOMIC POLICY